Uso racional del agua doméstica : análisis del consumo y uso del agua en Colombia (2020)
The industrial development and the exponential population growth are the main causes of aquatic ecosystems deterioration, negatively affecting the natural components and processes of this resource. Water is one of the most important basic needs for the human being. Therefore, if it does not accomplish the quality standards, it becomes a risk to public health. Nowadays a lot of people does not have access to drinking water, because of its poor quality, unequal distribution or the limited quantity available of this resource. The purpose of this work is to identify and determine the domestic water consumption in Colombia and which are the external parameters that justify the results. Based on domestic water consumption data in Colombia, it was calculated the average consumption in the country (197 l/(hab*day)), for each city and the devices that people use inside their homes, like toilet, washing machine, etc. As a result, it was found that...